2022
DOI: 10.1002/fsn3.2991
|View full text |Cite
|
Sign up to set email alerts
|

Study on the impact of temperature, salts, sugars and pH on dilute solution properties of Lepidium perfoliatum seed gum

Abstract: The functional properties of food gums are remarkably affected by the quality of solvent/cosolutes and temperature in a food system. In this work, for the first time, the chemical characterizations and dilute solution properties of Lepidium perfoliatum seed gum (LPSG), as an emerging carbohydrate polymer, were investigated. It was found that xylose (14.27%), galacturonic acid (10.70%), arabinose (9.07%) and galactose (8.80%) were the main monosaccharaide components in the LPSG samples. The uronic acid content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…We found that our value was 28 and 12% smaller compared to [ η ] values for XG reported by Khouryieh et al [ 14 ] and Bak et al [ 11 ], respectively. Compared to other polysaccharides in water, our [ η ] was in several cases much larger, such as with two data points from Potier et al for alginate and carboxymethyl cellulose, 600% and 300%, respectively [ 19 ], 400% for basil seed gum [ 20 ], 200% with guar gum [ 14 ], and 400% for lepidium perfoliatum seed gum [ 21 ]. In comparison to the [ η ] for K-carrageenan [ 22 ], the [ η ] for XG is quite similar, with less than 10% deviation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that our value was 28 and 12% smaller compared to [ η ] values for XG reported by Khouryieh et al [ 14 ] and Bak et al [ 11 ], respectively. Compared to other polysaccharides in water, our [ η ] was in several cases much larger, such as with two data points from Potier et al for alginate and carboxymethyl cellulose, 600% and 300%, respectively [ 19 ], 400% for basil seed gum [ 20 ], 200% with guar gum [ 14 ], and 400% for lepidium perfoliatum seed gum [ 21 ]. In comparison to the [ η ] for K-carrageenan [ 22 ], the [ η ] for XG is quite similar, with less than 10% deviation.…”
Section: Resultsmentioning
confidence: 99%
“…The general observation is that, as the ionic strength increases, XG structures tend to become more compact in configuration, as evidenced by the reduction of V E . The reduction in molecular dimension is a result of the charge screen effect on the electrostatic repulsions of the tri-saccharide side chains, leading to a more compact conformation [ 21 ]. This causes a decrease in the hydrodynamic coil radius of XG in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were then manually cleaned to remove all the impurities which visually could be identified. The Lepidium perfoliatum seed gum (LPSG) with average molecular weight of 2.34⨯10 5 Da was obtained according to the method described by Yousefi and Ako [2]. Xanthan gum with average molecular weight of 2 × 10 6 Da was purchased from Kelco (a division of Merck Co., New Jersey, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that xylose (14.27%), galacturonic acid (10.70%), arabinose (9.07%) and galactose (8.80%) are the main monosaccharaide components of LPSG. LPSG has 14.83% uronic acid and the average molecular weight of this biopolymer is 2.34 × 10 5 g/mol [5]. A shear-thinning behaviour of LPSG dispersions has been identified at various temperatures (5-65 °C) and concentrations (0.5-2%, w/w) [6].…”
Section: Introductionmentioning
confidence: 97%
“…L. perfoliatum dünya genelinde yayılış göstermekte ve ekimi yapılmaktadır. Bu bitkinin tohumları, farmasötik etkileri nedeniyle geleneksel tıp reçetelerinde uzun süredir kullanılmaktadır (Yousefi et al 2022). L. cartilagineum, halofit bir tür olarak kabul edilmektedir (Schmotzer 2021).…”
Section: Introductionunclassified